Removal of ammonia from atmosphere by air stripping with mesoporous silica-supported N-halamines. Issue 1 (February 2021) - Wang, Yingfeng; Jung, Joonhoo; Wen, Jianchuan; Ren, Xuehong; Sun, Yuyu
Abstract: Ammonia emission causes serious threats to human and environmental health, particularly in developing countries. In this work, the reactions of ammonia with two monomeric N-halamines, 1-chloro-5, 5–dimethylhydantoin (MCDMH) and 1-chloro-2, 2, 5, 5-tetramethyl-4-imidazolidinon (MC) in aqueous solution, and mesoporous silica-supported N-halamines (MSSNs) in aqueous and gaseous phase were investigated. For MCDMH (amide-based N-halamine), about 100% ammonia in aqueous solution was reduced under low molar ratio (Cl: N, 4:1) directly, which is 30% higher than MC (amine-based N-halamine). Nitrogen gas was the major product in the reaction between monomeric N-halamine and ammonia. In the case of MSSNs, up to 90% of ammonia (10 ppm, 10 mL) in aqueous solution could be reduced, and the major reaction product was monochloramine instead of nitrogen gas. In gaseous phase, MSSNs rapidly absorbed ammonia physically, and the N-halamines decomposed the absorbed ammonia under wet condition. These results point to the great potentials of MSSNs as good candidates to "catch" and decompose ammonia for a broad range of applications. Graphical Abstract: ga1 Highlights: Monomeric N-halamines showed high reactivity toward ammonia. Reaction mechanisms of monomeric and polymeric N-halamines with NH3 were different. Water molecule was the key factor of the reaction between MMSNs and ammonia.